APAC 2019 : proceedings of the 10th International Conference on Asian and Pacific Coasts, 2019, Hanoi, Vietnam - Trung Viet, Nguyen; Xiping, Dou; Thanh Tung, Tran; International Conference on Asian and Pacific Coasts 2019 : Hanoi, Vietnam) (Singapore : Springer, 2020)
This book presents selected articles from the International Conference on Asian and Pacific Coasts (APAC 2019), an event intended to promote academic and technical exchange on coastal related studies, including coastal engineering and coastal environmental problems, among Asian and Pacific countries/regions. APAC is jointly supported by the Chinese Ocean Engineering Society (COES), the Coastal Engineering Committee of the Japan Society of Civil Engineers (JSCE), and the Korean Society of Coastal and Ocean Engineers (KSCOE).
Keywords: COSTAS -- ASIA -- CONGRESOS; GEOTECTÓNICA -- OCÉANO PACÍFICO -- CONGRESOS; OCEANOGRAFÍA -- OCÉANO PACÍFICO -- CONGRESOS; MANEJO DE ZONAS COSTERAS -- ASIA -- CONGRESOS; MANEJO DE ZONAS COSTERAS -- REGIÓN DEL PACÍFICO -- CONGRESOS